Water Credit Analysis of Water Conservation Infrastructure Unit in Prumpung Watershed (DAS), Tuban District, East Java - Aldrianus, Wanca; Purwanto, Muhammad Yanuar Jarwadi (Jurnal Teknik Sipil dan Lingkungan, 2016)
Water credit is the activity to increase groundwater by increasing infiltration. The purpose of this research were to design and to analyse water credit of water conservation infrastructure unit in Prumpung DAS. The research consisted of prediction rainfall analysis, designing and water credit analysis of each water conservation infrastructure. The result showed that water credit of single artificial well unit were Rp 6.160.832 to Rp 9.555.674 per m3/year for mediterranean soil, Rp 30.804.158.249 to Rp 47.946.013.645 per m3/year for grumosol soil, and Rp 10.589 to Rp 16.464 per m3/year for regosol soil. Water credit of communal artificial well unit were Rp 10.498.475 to Rp 11.200.082 per m3/year for mediterranean soil, Rp 52.492.374.552 to Rp 56.443.974.147 per m3/year for grumosol soil, and Rp 17.426 to Rp 19.194 per m3/year for regosol soil. Water credit of rorak unit were around Rp 198.701 per m3/year for mediterranean soil and Rp 993.514.151 per m3/year for regosol soil. Water credit of water retention unit were around Rp 14.16 per m3/year for mediterranean soil, Rp 2.125 per m3/year for grumosol soil and Rp. 850 per m3/year for regosol soil.